Exploring the relationship of marketing & technological innovation on store equity, word of mouth and satisfaction - Amgad S. D. Khaled; Salma Ahmed; Mohd. Azmi Khan; Eissa A. Al-Homaidi; Ahmad Moh'd Mansour (Cogent Business & Management, 2021)
While innovation affects company efficiency, research into service innovation is scarce and lacks consensus. In retailing, in latest years, innovation has aroused significant interest in corporate and academic world. This research analyses retail experience innovation from the perspective of marketing innovation and technological innovation perspectives to comprehend its effect on satisfaction. The main goal of this research is to explore the relationship between technological and marketing innovation, word-of-mouth and satisfaction through three key constructs: brand store equity, customer value and store image. A total of 315 retail clients from grocery, apparel, furnishings and electronics shops were covered for the study on which multiple regression was used. The study found that technological innovation was important for shaping image, value and satisfaction compared to marketing innovation. Simultaneously, shop image had the biggest effect on customer satisfaction and satisfaction is a very essential ingredient for word-of-mouth behaviour (WOM-Referral and activity).
Keywords: 650; Innovation; satisfaction; retailing; store brand equity; consumer value; WOM behaviour; technological innovation; marketing innovation